A pro-oxidant property of vitamin C to overcome the burden of latent Mycobacterium tuberculosis infection: A cross-talk review with Fenton reaction - Gaglani, Pratikkumar; Dwivedi, Manish; Upadhyay, Tarun Kumar; Kaushal, Radhey Shyam; Ahmad, Irfan; Saeed, Mohd (Frontiers in Cellular and Infection Microbiology, 2023)
Tuberculosis (TB), caused by the bacillus M. tuberculosis, is one of the deadliest infectious illnesses of our day, along with HIV and malaria.Chemotherapy, the cornerstone of TB control efforts, is jeopardized by the advent of M. tuberculosis strains resistant to many, if not all, of the existing medications.Isoniazid (INH), rifampicin (RIF), pyrazinamide, and ethambutol are used to treat drug-susceptible TB for two months, followed by four months of INH and RIF, but chemotherapy with potentially harmful side effects is sometimes needed to treat multidrug-resistant (MDR) TB for up to two years. Chemotherapy might be greatly shortened by drugs that kill M. tuberculosis more quickly while simultaneously limiting the emergence of drug resistance.Regardless of their intended target, bactericidal medicines commonly kill pathogenic bacteria (gram-negative and gram-positive) by producing hydroxyl radicals via the Fenton reaction.Researchers have concentrated on vitamins with bactericidal properties to address the rising cases globally and have discovered that these vitamins are effective when given along with first-line drugs. The presence of elevated iron content, reactive oxygen species (ROS) generation, and DNA damage all contributed to VC’s sterilizing action on M. tb in vitro. Moreover, it has a pleiotropic effect on a variety of biological processes such as detoxification, protein folding – chaperons, cell wall processes, information pathways, regulatory, virulence, metabolism etc.In this review report, the authors extensively discussed the effects of VC on M. tb., such as the generation of free radicals and bactericidal mechanisms with existing treatments, and their further drug development based on ROS production.